Structural engineering of luminogens with high emission efficiency both in solution and in the solid state - Wu, Hongwei (2020)
Developing molecules with high emission efficiency both in solution and the solid state is still a great challenge, since most organic luminogens are either aggregation-caused quenching or aggregation-induced emission molecules. This dilemma was overcome by integrating planar and distorted structures with long alkyl side chains to achieve DApAD type emitters. A linear diphenyl–diacetylene core and the charge transfer effect ensure considerable planarity of these molecules in the excited state, allowing strong emission in dilute solution (quantum yield up to 98.2%). On the other hand, intermolecular interactions of two distorted cyanostilbene units restrict molecular vibration and rotation, and long alkyl chains reduce the quenching effect of the p–p stacking to the excimer, eventually leading to strong emission in the solid state (quantum yield up to 60.7%).